Molecular Traits and Functional Analysis of the CLAVATA3/Endosperm Surrounding Region-Related Small Signaling Peptides in Three Species of Gossypium Genus - Lin, Huan; Wang, Wei; Chen, Xiugui; Sun, Zhenting; Han, Xiulan; Wang, Shuai; Li, Yan; Ye, Wuwei; Yin, Zujun (Frontiers in Plant Science, 2021)
The CLAVATA3/endosperm surrounding region-related (CLE) small peptides are a group of C-terminally encoded and post-translationally modified signal molecules involved in regulating the growth and development of various plants. However, the function and evolution of these peptides have so far remained elusive in cotton. In this study, 55, 56, and 86 CLE genes were identified in the Gossypium raimondii, Gossypium arboreum, and Gossypium hirsutum genomes, respectively, and all members were divided into seven groups. These groups were distinctly different in their protein characteristics, gene structures, conserved motifs, and multiple sequence alignment. Whole genome or segmental duplications played a significant role in the expansion of the CLE family in cotton, and experienced purifying selection during the long evolutionary process in cotton. Cis-acting regulatory elements and transcript profiling revealed that the CLE genes of cotton exist in different tissues, developmental stages, and respond to abiotic stresses. Protein properties, structure prediction, protein interaction network prediction of GhCLE2, GhCLE33.2, and GhCLE28.1 peptides were, respectively, analyzed. In addition, the overexpression of GhCLE2, GhCLE33.2, or GhCLE28.1 in Arabidopsis, respectively, resulted in a distinctive shrub-like dwarf plant, slightly purple leaves, large rosettes with large malformed leaves, and lack of reproductive growth. This study provides important insights into the evolution of cotton CLEs and delineates the functional conservatism and divergence of CLE genes in the growth and development of cotton.